2007
DOI: 10.1353/hub.2007.0048
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causes of Chronic Energy Deficiency and Obesity in Women of India

Abstract: We investigate the nutritional status of women in India and its relation to the prevalence of chronic energy deficiency (CED) and obesity. To do this, we have used the data from the Indian National Family Health Survey, 1998-1999, on body mass index (BMI) of ever-married women, ages 15-49 years, along with several socioeconomic factors, such as level of education, religion or caste, occupational status, and standard of living index. The study was based on 81,712 women from 26 states and 6 zones, which were gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 30 publications
7
41
1
Order By: Relevance
“…A lower prevalence of obesity has been reported than the present study among the Bengalee 13 and Kayastha 32 populations. In contrast, the prevalence of overweight was significantly higher than those reported for Indian 33 , Rengma Naga 16 and Nyishi tribal 8 women. The prevalence of obesity was observed to be significantly higher than those reported from Tangkul Naga 11 and Nyishi tribal 8 women.…”
Section: Discussioncontrasting
confidence: 76%
“…A lower prevalence of obesity has been reported than the present study among the Bengalee 13 and Kayastha 32 populations. In contrast, the prevalence of overweight was significantly higher than those reported for Indian 33 , Rengma Naga 16 and Nyishi tribal 8 women. The prevalence of obesity was observed to be significantly higher than those reported from Tangkul Naga 11 and Nyishi tribal 8 women.…”
Section: Discussioncontrasting
confidence: 76%
“…Studies have consistently reported that prevalence of CED was very high among women from India. Using data from the Indian National Family Health Survey [68], Bharati et al [69] reported an overall prevalence of CED of 31.20% among women aged 15-49 years. The prevalence of CED was high (20-39%) among Bengalee women as observed by Bose et al [70].…”
Section: Discussionmentioning
confidence: 99%
“…Responses to energy shortfalls are best understood in humans, in which, while mortality risk is clearly associated with malnutrition (Nieburg et al 1992;Young and Jaspars 1995), many populations in developing countries survive and reproduce successfully with average energy intakes below current recommendations (Durnin et al 1973;Durnin 1979;Edmundson 1980;Schofield and Lambert 1975;Waterlow 1986;WFP 2007). In India, for example, 31.2% of women suffer from chronic energy deficiency (Bharatu et al 2007), yet the country's population grew from 863 million in 1990-1992 to 1050 million in 2001(WFP 2007. Further, a recent study on captive rhesus macaques (Macaca mulatta), fed on a calorie-restricted diet 30% lower than their baseline diet for a period of 20 yr, showed that age-related pathologies were reduced and longevity increased in the calorie-restricted group, compared to controls (Colman et al 2009).…”
Section: Discussionmentioning
confidence: 99%